Outcomes and complications of medical thoracoscopy in undiagnosed exudative pleural effusion - Mona M. Ahmed; Hesham Atef Abdel Halim; Ehab Thabet Aziz; Rania Mohammed El-Shorbagy (The Egyptian Journal of Bronchology, 2016)
Abstract Background Thoracoscopy has long been established as the procedure of choice for various chest diseases, among which is undiagnosed pleural effusions. Thoracoscopy does not only visualizes the extent of the disease but allows adequate tissue biopsy sampling. Objective The aim of the present study was to detect outcomes and complications of medical thoracoscopy in undiagnosed pleural effusion. Patients and methods This study was conducted on 50 patients with unexplained exudative pleural effusion referred for medical thoracoscopy at Abbassia Chest Hospital. Results Medical thoracoscopy is a safe and valuable tool for the diagnosis of pleural effusion, particularly for patients with suspected malignancy. Overall cost-effectiveness of thoracoscopy is better due to its better yield and lesser duration of hospital stay. Medical thoracoscopy gave a definitive diagnosis with a diagnostic yield of 96%. Histopathological results of thoracoscopic pleural biopsy revealed that the most common diagnosis was malignancy (92%), followed by tuberculous pleurisy (2%), and fibrotic pleurisy (2%); only 4% of the patients remained undiagnosed. The most common malignant pathological type was malignant pleural mesothelioma (60%), followed by metastatic adenocarcinoma (12%). According to the residence of studied patients, we found that environmental exposure to asbestos has a relationship with mesothelioma in patients living in Shoubra El-Kheima and Helwan. Medical thoracoscopy is a safe tool for diagnosing pleural effusion; although no major complications were found in the present study, minor complications occurred only in 10% of the patients. Conclusion Medical thoracoscopy is a valuable tool in the diagnosis of undiagnosed pleural effusion. It is a simple and safe method with a high diagnostic yield and low complication rates.